Robot-Assisted Extraperitoneal Ventral Hernia Repair—Experience From the First 160 Consecutive Operations With Lateral eTEP and eTAR Techniques - Robert Vogel; Frank Heinzelmann; Peter Büchler; Björn Mück (Journal of Abdominal Wall Surgery, 2024)
IntroductionThere is a growing consensus on the benefits of retro-muscular (RM) mesh positioning, highlighted by its recommendation in the latest edition of EHS guidelines. The eTEP method has facilitated minimally invasive hernia repairs with retro-muscular mesh placement. With the increasing availability of robotic systems, there has been a corresponding increase in robotic adaptations of minimally invasive techniques involving retro-muscular mesh placement.Materials and MethodsAll patients who underwent robotic ventral hernia repair using the lateral extraperitoneal eTEP technique at Kempten Hospital between September 2019 and December 2023 were includes in the study. Preoperative characteristics, perioperative parameters, postoperative parameters, and hernia-specific parameters, were retrospectively analyzed using the hospital information system.Results160 patients were operated using a lateral approach eTEP technique during the observation period, 111 (69.38%) for incisional hernia repair and 49 (30.63%) for primary hernia repair. 43 cases required TAR (30 unilateral TAR and 13 bilateral TAR). 139 patients had a medial (86.98%), seven patients (4.14%) a lateral and 14 patients (8.88%) a combined hernia defect. The median operative time was 143 min (range: 53 min–495 min). The median length of hospital stay was 3 days (range: 2–16). There was one intraoperative complication. The postoperative complication rate was 6.25% (10 patients), with 1.72% (2 patients) requiring reoperation. Sonographic follow-up examinations revealed seromas in 5 patients, with 4 located in the retromuscular mesh space and 1 in the former hernia sac. None of these seromas required surgical intervention.ConclusionThe “lateral approach” of robotic eTEP provides a safe surgical method for treating ventral hernias using minimally invasive techniques and mesh augmentation in the retro-muscular space. Further studies are necessary to compare extraperitoneal with transperitoneal methods.